2022
DOI: 10.3390/idr14060100
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Antibody Status at the Time of Hospital Admission and the Prognosis of Patients with COVID-19: A Prospective Observational Study

Abstract: The association between COVID-19 severity and antibody response has not been clearly determined. We aimed to assess the effects of antibody response to SARS-CoV-2 S protein at the time of hospital admission on in-hospital and longitudinal survival. Methods: A prospective observational study in naive hospitalised COVID-19 patients. The presence of anti-S SARS-CoV-2 IgM and IgG was evaluated using a lateral flow assay at the time of admission. The patients were followed up for 8–30 months to assess survival. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In patients who died from COVID-19, the level of CRP was about 10 times higher than in those who recovered [ 24 ]. Moreover, in severe infections, CRP levels were associated with higher anti-spike IgG antibody titers [ 23 , 24 , 25 , 26 ]. In our study, the CRP levels moderately correlated with anti-S IgG but not at all with anti-N IgG, despite the high anti-N IgG titers.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who died from COVID-19, the level of CRP was about 10 times higher than in those who recovered [ 24 ]. Moreover, in severe infections, CRP levels were associated with higher anti-spike IgG antibody titers [ 23 , 24 , 25 , 26 ]. In our study, the CRP levels moderately correlated with anti-S IgG but not at all with anti-N IgG, despite the high anti-N IgG titers.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that studies correlating more severe disease to more vigorous antibody response in COVID-19, are performed using laboratory tests, and not LFIAs, to assess the antibody titer [90] . Recently Jurenka and co-workers using a LFIA kit assessed anti-S SARS-CoV-2 antibodies in hospitalized patients and found that the absence of IgM and IgG at the time of admission predicted in-hospital mortality [91] . However, results from this study are in sharp contrast with previous findings [68] .…”
Section: Performance and Reliability Of Lfia In Post-infectionmentioning
confidence: 99%
“…A large number of studies evaluated the accuracy of LFIA for antibody detection compared to ELISA, CLIA or RT-PCR and some meta-analyses and reviews have summarized results of these studies [11] , [84] , [86] , [91] [95] . Deeks and colleagues in an early Cochrane review, including sparse data collected in various time ranges from the disease onset, found inconsistencies between the available assays, however, POCs had higher pooled sensitivity than ELISA for IgG and IgG-IgM [86] .…”
Section: Performance and Reliability Of Lfia In Post-infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed dynamics of the antibody response to SARS-CoV-2 have been identified as a predictor of poor outcomes, possibly impairing the ability to fully recover from the disease. An association between delayed antibody response and disease severity and the extent of organ damage has been proposed [12,13]. The impact of delayed antibody response on QoL in COVID- 19 survivors is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%